WOMEN ENTREPRENEURSHIP - Claudia-Marinela ZĂTREANU (Management & Marketing)
Women entrepreneurship is an important area being globally recognized as one of the most important measures of economic growth and, implicitly, of decreasing the level of poverty. Incentivizing women to start their own business is essential for the development of women entrepreneurship and it’s also a strategic objective at European level, assumed by Romania as an EU member state. In order to have access to the same opportunities as men, women have to go beyond a series of obstacles, one of which is family responsibility, which often returns to their care. Therefore, this paper approaches a wide variety of themes that correspond to the present, such as motivation, obstacles encountered and also the advantages and disadvantages that come with the entrepreneurial profession, using as a research method the interviews with women entrepreneurs.